Modelos anatómicos – carrera de terapia física - Llivi Ruilova, Danny Vicente (2023)
On July 27 of the current year, he enrolled in the Physical Therapy course at the Faculty of Health and Human Sciences, directed by Mgt. Cynthia Pilco Toscano, anatomical models, acquired through self-management through the UEB Public Company, in order to strengthen the knowledge of students.